La indemnización dentro del juicio de daño moral y su incidencia en la reparación integral de la persona ofendida en la unidad judicial civil del Cantón Riobamba durante el período 2013 a 2014. - Martinez Vizuete, Danilo Marcial (2016)
The present research work shows how affects the compensation within the judgment of moral damage and its impact in the repair of the offended person in the Civil Judicial unit of the Riobamba Canton period 2013 to 2014. The research structure is divided into four chapters: first chapter develops the Framework where there is a problem, its origin, as it is presented and how it behaves, after general objectives and specific objectives in order to determine if the compensation within the judgment of Moral damage affects the offended person repairing; also the problem where we observed that the research is feasible, original and timely carry out is justified. The second chapter develops the Theoretical Framework where you applied the instrument of the signing which was doctrine, theories, concepts, and bibliographic items drawn from books, regulations, texts and laws, i.e., come to constitute the conceptual, theoretical, legal and doctrinal part of the research; It is divided into four units with their respective subunits; in the first unit we will discuss MORAL DAMAGE; on the second drive, we will refer to THE COMPENSATION OF THE MORAL DAMAGE; in the third unit, we will mention THE IMPACT OF THE COMPENSATION IN THE PERSON OFFENDED; and the fourth LOOK AT CASES PRACTICAL WITH RELATIONSHIP TO THE TRIALS OF DAMAGE MORAL UNIT. Third chapter, Research implementation, through the surveys application to lawyers in free exercise based on a questionnaire or survey in order to determine if the compensation within the judgment of moral damage affects to offended person repairing; as well as the implementation of the interviews, because it used a direct discussion with the judges of the unit Judicial Civil of the Canton Riobamba, using the interview guide was where appropriate the use of inductive and analytical method; already that through interviews and the inductive method was obtained information that helped to identify a particular way the influence of the compensation within the trial of moral damage and its incidence in the repairing of the offended person; While applying the analytical method was a critical and legal analysis of all of the aspects investigated which served to verify the hypothesis. The fourth chapter provides the Conclusions and Recommendations achieved by the results interpretation and discussion permitted according to the application of pictures and statistical graphics; as well as, the use of the software package of excel through which we obtained exact data processing percentages, i.e., that research by its very nature is descriptive because after tabulating, interpreting and processing the information problem described as appears and behaves in its context and explanatory because then the tabulated and calculated results were described.